Haji Abdul Malik Karim Amrullah (HAMKA) dan Ekonomi Islam: Studi Pada Karya Keadilan Sosial dalam Islam - Rahmad Hakim (Universitas Muhammadiyah Malang, 2018)
This paper aims to explore Islamic economic thought Haji AbdulMalik Karim Amrullah in his work on Social Justice in Islam. Based onthe study conducted, research on the history of Islamic economicthought in Indonesia is still a little done. These considerations make thisresearch important to do. This type of research is qualitative with acharacter study approach (biography), the method of collecting data isobtained by documentation - that is, a study of the work of social justicein Islam Haji Abdul Malik Karim Amrullah. The result of the study asfollows: first, that property ownership belongs to God, while humansare only managers of these assets. Secondly, there are three principles ofIslamic economics according to Hamka, namely: justice, free to act andfreedom.